High plasma leptin levels are associated with impaired diastolic function in patients with coronary artery disease - Puurunen, V.P.; Lepojärvi, E.S.; Piira, O.P.; Hedberg, P.; Junttila, M.J.; Ukkola, O.; Huikuri, H.V. (Peptides (New York, N.Y. : 1980), 2016)
•High leptin levels are associated with impaired LV diastolic function in CAD.•Leptin may be a mechanistic link between obesity and congestive heart failure.•Leptin may have profibrotic effects and increase collagen in myocardial ECM. Obese subjects have elevated leptin levels, which have been associated with increased risk of cardiovascular events. Because leptin has direct cellular effects on various tissues, we tested the hypothesis that leptin levels are associated with cardiac structure or function in patients with coronary artery disease (CAD). The study population consisted of 1 601 CAD patients, of whom 42% had type 2 diabetes mellitus. Plasma leptin was measured in fasted state and an echocardiography performed. Leptin levels were not related to LV dimensions or LV ejection fraction (NS for all), but higher leptin levels were associated with elevated E/E’ (9.43 vs. 11.94 in the lowest and the highest leptin quartile, respectively; p=0.018 for trend). Correspondingly, a decreasing trend was observed in E/A (1.15 vs. 1.06; p=0.037). These associations were independent of obesity and other relevant confounding variables. We conclude that elevated plasma leptin levels are associated with impaired left ventricular diastolic function in patients with CAD independently of obesity and other confounding variables. Leptin may be one of the mechanistic links explaining the development of congestive heart failure in obese subjects.